International Brethren conference on missions ; 3 - Dyer, Kevin; Allan, John; Lowman, Pete; International Brethren conference on Missions Singapore July 1993 (1993)
Contents : tape 3 : "Troubled waters" / Kevin Dyer "Frontiers of mission"/ John Allan ""/ Pete Lowman
Keywords: Brethren movement -- missions -- congresses